Underdosing of Surfactant for Preterm Babies with Respiratory Distress Syndrome in Clinical Practice: A Retrospective Cohort Study - Boix, Hector; Rite, Segundo; Arruza, Luis; Fernandez, Cristina; Serrano, Itziar; Baquedano, Irene; Sanchez, Ana; Ferreira, Erika; Fernandez, Patricia; Gonzalez, Rosa; Elorza, M. Dolores (American Journal of Perinatology, 2019)
Objective To evaluate the initial doses of surfactant administered to preterm infants with respiratory distress syndrome.Study Design This is a retrospective cohort study of 206 preterm infants admitted in four level III neonatal intensive care units of acute tertiary care hospitals in Spain between 2013 and 2015.Results The mean initial dose of surfactant was 173.9 (37.3) mg/kg, and 47.5% of infants received a dose of 200 mg/kg ± 10% (180–220 mg/kg), 47% less than 180 mg/kg (–10%), and 5.4% more than 220 mg/kg (+10%). Very preterm infants (<28 weeks) received higher initial doses than more mature infants, but in all cases, the mean doses were below the recommended 200 mg/kg (by 9.2% in gestational age 23–28 weeks, by 15.9% in 29–32 weeks, and by 24.3% in >32 weeks).Conclusion Administration of surfactant below the prescribed dose is a frequent error in clinical practice. Inadvertently rounding down doses seems a plausible explanation.
Keywords: dosage; preterm babies; respiratory distress syndrome; surfactant